2013
DOI: 10.1124/mol.113.089821
|View full text |Cite
|
Sign up to set email alerts
|

Novel Small Molecule Inhibitors of TLR7 and TLR9: Mechanism of Action and Efficacy In Vivo

Abstract: The discovery that circulating nucleic acid-containing complexes in the serum of autoimmune lupus patients can stimulate B cells and plasmacytoid dendritic cells via Toll-like receptors 7 and 9 suggested that agents that block these receptors might be useful therapeutics. We identified two compounds, AT791 {3- [4-(6-(3-(dimethylamino)that inhibit Toll-like receptor (TLR)7 and 9 signaling in a variety of human and mouse cell types and inhibit DNA-TLR9 interaction in vitro. When administered to mice, these compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(109 citation statements)
references
References 30 publications
(39 reference statements)
2
99
1
Order By: Relevance
“…It has been reported that TLR7 and TLR9 ligands induced inflammations are inhibited by CQ/HCQ in macrophages [48,49]. CQ inhibits TLR3-induced biological response and TLR2-mediated antigen cross-presentation in immune cells [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that TLR7 and TLR9 ligands induced inflammations are inhibited by CQ/HCQ in macrophages [48,49]. CQ inhibits TLR3-induced biological response and TLR2-mediated antigen cross-presentation in immune cells [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of the latter was recently challenged in a study demonstrating that the inhibitory effect of HCQ is secondary to its direct binding to nucleic acids when concentrated within the endosome, thereby preventing ligands from binding to TLRs [32,33]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, recombinant DNA and RNA sensor proteins allow for direct binding assays to differentiate receptor-binding compounds from compounds that affect DNA-and RNAsensing pathways by a receptor-independent mode of action. In a recent example of TLR9 antagonists, suppressive activity was shown to depend on interaction of TLR9 antagonists with DNA and accumulation in endosomes 117 .…”
Section: Tlr Antagonists In Autoimmune Diseases and Lymphomamentioning
confidence: 99%